2008
DOI: 10.1080/00207450601042177
|View full text |Cite
|
Sign up to set email alerts
|

Time Reproduction Disturbances in Adhd Children: An Erp Study

Abstract: Sixteen ADHD children and a control group were asked to reproduce the varying time duration of successively presented visual stimuli. Time estimation was poorer in ADHD children, who showed more impulsive errors. ERPs exhibited similar grand-mean waveforms for both groups during the estimating period, but they were significantly different during the reproducing stage, when an early positive wave over frontal regions characterized the control group, interpreted as memory-guided motor output, followed by a slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In addition, our data indicated that the SMA may be one of the key cerebral regions for attention-dependent quantification of time perception, though further neuroimaging studies are required to verify this source localization result in this study. The current findings improve our understandings of timing mechanisms and lay the ground for the investigation of patients with time perception deficits, such as attention-deficit hyperactivity disorder and Parkinson’s disease [41,42]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data indicated that the SMA may be one of the key cerebral regions for attention-dependent quantification of time perception, though further neuroimaging studies are required to verify this source localization result in this study. The current findings improve our understandings of timing mechanisms and lay the ground for the investigation of patients with time perception deficits, such as attention-deficit hyperactivity disorder and Parkinson’s disease [41,42]. …”
Section: Discussionmentioning
confidence: 99%
“…The literature has often described that children with ADHD have deficits in the production and reproduction of time [17][18][19] , however, there is still no consensus about these alterations [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the participants was 12.89 years (8 No significant intergroup differences were observed in age, IOWA CPRS, and IQ scores (Table 1). Statistically significant differences were observed in K-ARS and ADS.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, accurate representation of transient information is required to accomplish the ability to plan and organize adequate sequences of behavioral actions. 8) Time perception is often mea-…”
Section: Introductionmentioning
confidence: 99%